2017
DOI: 10.1093/jac/dkx313
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of nitrofurantoin at different pH levels against pathogens involved in urinary tract infections

Abstract: Nitrofurantoin bactericidal activity against Enterobacteriaceae significantly increases at lower pH levels. Bactericidal activity of nitrofurantoin may be overestimated or underestimated, which may have implications for therapy and the interpretation of clinical breakpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The present study extends the antibiotic potentiating activity of the cinnamon derived proanthocyanidin to nitrofurantoin. Since it was reported that pH plays a vital role in the antibacterial activity of nitrofurantoin (Fransen et al, 2017 ), the synergy studies were conducted in a range of pH from 5.2 to 7.6. In order to establish synergy mathematically, two models were considered—Fractional Inhibitory Concentration Index and Bliss independence model (Kaur et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study extends the antibiotic potentiating activity of the cinnamon derived proanthocyanidin to nitrofurantoin. Since it was reported that pH plays a vital role in the antibacterial activity of nitrofurantoin (Fransen et al, 2017 ), the synergy studies were conducted in a range of pH from 5.2 to 7.6. In order to establish synergy mathematically, two models were considered—Fractional Inhibitory Concentration Index and Bliss independence model (Kaur et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antibiofilm activity at a very low concentration of TAP directed toward the evaluation of potentiating activity of TAP with the known frontline antibiotic, NIT. Previous reports state that the effective pH of nitrofurantoin activity is 5.5-6.5 (Fransen et al, 2017). Thus, the synergy activity was tested in different pH (5.2, 5.8, 6.4, 7.0, and 7.6) in a time-dependent manner.…”
Section: Potentiation Of Nitrofurantoin By Tap-ph-dependent Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Maximum urine concentrations are around 100 mg/L, but vary between 15-230 mg/L, occurring 3-10 h after dosing, but heavily dependent on formulation and fasting status [165]. Activity is enhanced under acidic conditions [166]. Nitrofurantoin is well tolerated with mild gastrointestinal side effects (in 5-16%).…”
Section: Nitrofurantoinmentioning
confidence: 99%